PENDAMPINGAN EDUKASI KREATIVITAS TEKNIK LUKIS BATIK GUTTA KEPADA JEMAAT WANITA DI GEREJA UTUSAN PANTEKOSTA BANDUNG - Aryani, Dewi Isma; Fatimah, Dina; Tjandra, Miki; Agustine, Saskia Putri (Abdi Seni, 2025)
Through joint community service projects, Universitas Kristen Maranatha and Universitas Komputer Indonesia (UNIKOM) Bandung educate female congregation partners from the Gereja Utusan Pantekosta Bandung on the creative uses of gutta batik painting techniques. ISTANA KAEN industrial partners are involved in this activity and support to provide all participants' demands for fabric. Mentoring is the method employed in PkM. Four faculty members and sixteen FSRD student volunteers made up the service team for the offline PkM implementation. Additional members included one faculty member from Universitas Kristen Maranatha's Bachelor of Information Systems Program and one faculty member from the Bachelor of Management Program., also one faculty member from UNIKOM's Bachelor of Interior Design Program. Twenty female members of the Gereja Utusan Pantekosta Bandung congregation participated in this activity. The PkM process is completed in the Even semester of 2023–2024 and takes around three months from planning to implementation. The outcomes of this PkM are expected to demonstrate how the gutta batik painting method may foster creativity and enhance artistic abilities in all female congregation members at the Gereja Utusan Pantekosta Bandung. The primary goal of this activity is to increase participants' awareness of artistic creativity values, particularly as it relates to gutta batik painting techniques.